Analysis of Petroleum Downstream Industry Potential in Riau Province - Tomi Erfando; Ira Herawati (Journal of Geoscience, Engineering, Environment, and Technology, 2017)
Petroleum downstream industry in Riau Province is still not optimal. The data shows that from 98,892,755 barrels lifting oil each year only 62,050,000 barrels could be processed in refinery unit II Dumai operated by PT Pertamina. There is a potential of 35-40% of downstream industry. Indonesian Government through The Ministry of Energy and Mineral Resources declared the construction of a mini refinery to boost oil processing output in the downstream sector. A feasibility study of development plan mini refinery is needed. The study includes production capacity analysis, product analysis, development & operational refinery analysis and economic analysis. The results obtained by the mini refinery capacity is planned to process crude oil 6000 BOPD with the products produced are gasoline, kerosene, diesel and oil. Investment cost consist of is capital cost US $ 104419784 and operating cost US $ 13766734 each year with net profit earned US $ 12330063/year and rate of return from investment 11.63%